Biomass gasification of sugarcane bagasse and empty fruit bunch the effect of operating temperature and particle - Linggang, Diana (2012)
Depletion of fossil fuel as the source of energy has opened the door to the research of various abundant,potential and valuable sources of energy. Therefore,biomass gasification to produce either liquid or gases fuel has been widely investigated.The production of hydrogen from biomass gasification of agricultural waste which are sugarcane bagasse (SCB) and empty fruit bunch (EFB) has been studied by using small lab scale gasification.There were 12 series of experiments run to investigate the effects of operating temperature at 600˚C, 700˚C, 800˚C and 900˚C and three different particle sizes (0.3 mm, 0.6 mm, and 1.0 mm) of both raw materials.The gasification unit which consists of turbulent furnace and a micro glass reactor were used and nitrogen (N2) was supplied as the carrier gas and oxygen (O2) was used as the gasifier agent.Both samples were reduced in the moisture content after drying process. The characteristic of both raw materials was identified using thermo gravimetric analyzer (TGA) to determine volatility, moisture content, thermal stability and the decomposition kinetics of the samples.The fix sample size of 1.0 g and N2/O2 ratio of 9:1 was used in the experiment. From the experiment,it was found that the particle size of 0.3 mm and the operating temperature of 800˚C were producing more hydrogen for gasification of EFB and particle size of 0.3 mm with 900˚C for gasification of SCB, compared to other particle size or operating temperature. This is because the smaller particle size gives more surface area to react in partial oxidation process and there is more energy supply at the high operating temperature to break the complex long chain bond of lignincellulosic biomass into the simplest carbon chain of syngas. Amount of ash from the experiment was analyzed to identify the ash content in the raw materials.The study conducted showed the potential of local agricultural waste as a raw material in producing hydrogen via biomass gasification.